2017
DOI: 10.1002/adfm.201606215
|View full text |Cite
|
Sign up to set email alerts
|

“Naked” Magnetically Recyclable Mesoporous Au–γ‐Fe2O3 Nanocrystal Clusters: A Highly Integrated Catalyst System

Abstract: Naked magnetically recyclable mesoporous Au–γ‐Fe2O3 clusters, combining the inherent magnetic properties of γ‐Fe2O3 and the high catalytic activity of Au nanoparticles (NPs), are successfully synthesized. Hydrophobic Au–Fe3O4 dimers are first self‐assembled to form sub‐micrometer‐sized Au–Fe3O4 clusters. The Au–Fe3O4 clusters are then coated with silica, calcined at 550 °C, and finally alkali treated to dissolve the silica shell, yielding naked‐Au–γ‐Fe2O3 clusters containing Au NPs of size 5–8 nm. The silica p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…On these grounds, the making of tailor-made PdNPs assemblies can be successfully achieved. Overall, the surfactant plays a critical role in forming the wellordered PdNPs-decorated assemblies, as it can effectively prevent aggregation of the PdNPs, and thereby, ensure good NPs dispersibility in the assemblies [55][56][57] ; importantly, it also directs the formation of specific structures. We now focus on the physiochemical property of the PdNPs assemblies and their environment implications as nanoreactors for effective water remediation.…”
Section: Simultaneous Removal and In Situ Catalytic Dechlorination mentioning
confidence: 99%
“…On these grounds, the making of tailor-made PdNPs assemblies can be successfully achieved. Overall, the surfactant plays a critical role in forming the wellordered PdNPs-decorated assemblies, as it can effectively prevent aggregation of the PdNPs, and thereby, ensure good NPs dispersibility in the assemblies [55][56][57] ; importantly, it also directs the formation of specific structures. We now focus on the physiochemical property of the PdNPs assemblies and their environment implications as nanoreactors for effective water remediation.…”
Section: Simultaneous Removal and In Situ Catalytic Dechlorination mentioning
confidence: 99%
“…[23] However,i n this work, the size of iron oxide NPs was kept below the critical size (25 nm) needed for a-Fe 2 O 3 formation. [24] Figure 1(c) confirms that the iron oxide crystal grains on the 3DPCF are about 20 nm, that is, smaller than 25 nm. Furthermore, Philip et al demonstrated that NaOH in the sample can increaset he Fe 2 O 3 phase transition temperature.…”
Section: Resultsmentioning
confidence: 52%
“…To visualize the performance of the catalyst directly, the data in Figure 7 (a) are processed. Since the concentration of NaBH 4 in the reaction system far exceeds that of 4-NP, the rate A t A 0 ¼ −kt: [40,41] Where A t and A 0 are 4-NP absorbance at reaction time t and initial time 0, respectively. k is the rate constant.…”
Section: Resultsmentioning
confidence: 99%